Identification of anti-syntaxin 5 autoantibody as a novel serum marker of endometriosis - Nabeta, Motowo; Abe, Yasuhito; Takaoka, Yuki; Kusanagi, Yasuki; Ito, Masaharu (Journal of Reproductive Immunology, 2011)
The sensitivity and specificity of CA125, as a sole serum marker of endometriosis, are not high enough for routine clinical assessment. To explore new markers for the diagnosis of endometriosis, serum autoantibodies in endometriotic patients were investigated employing a fibroblast cell line, two-dimensional (2D) gel electrophoresis and Western blotting. Proteins reacting with serum autoantibodies by Western blotting were identified using MASCOT analysis. ELISAs were then prepared using recombinant proteins and titers of serum autoantibodies were determined in the endometriotic patients, disease controls, and healthy subjects. Among the autoantibodies identified, anti-syntaxin 5 (STX5) autoantibody levels were significantly elevated in endometriotic patients. Sensitivity (53.6%) and accuracy (72.2%) of the serum anti-STX5 autoantibody assay were better than those of serum CA125 levels (36.2% and 62.9%, respectively) for diagnosis. The sensitivity of anti-STX5 autoantibody was remarkably high in Stage II (80.0%) compared with that of CA125 (40.0%). A combination assay of anti-STX5 autoantibody with CA125 improved the overall sensitivity to 69.6%. We conclude that serum anti-STX5 autoantibody, which was discovered by a proteomic approach, is a potential new serum marker for the diagnosis of endometriosis. This initial study now requires validation by further clinical evaluation.